Clinical and Haemodynamic Effects of Arteriovenous Shunts in Patients with Heart Failure with Preserved Ejection Fraction - Medhat Soliman; Nizar Attallah; Houssam Younes; Woo Sup Park; Feras Bader (Cardiac Failure Review)
The arteriovenous shunt (AVS) is the most commonly used vascular access in patients receiving regular haemodialysis. The AVS may have a significant haemodynamic impact on patients with heart failure. Many studies have sought to understand the effect of AVS creation or closure on heart structure and functions, most of which use non-invasive methods, such as echocardiography or cardiac MRI. Data are mainly focused on heart failure with reduced ejection fraction and there are limited data on heart failure with preserved ejection fraction. The presence of an AVS has a significant haemodynamic impact on the cardiovascular system and it is a common cause of high-output cardiac failure. Given that most studies to date use non-invasive methods, invasive assessment of the haemodynamic effects of the AVS using a right heart catheter may provide additional valuable information.